2014
DOI: 10.1159/000364781
|View full text |Cite
|
Sign up to set email alerts
|

Drug Fever due to a Single Dose of Pantoprazole

Abstract: Although proton pump inhibitors (PPI) are generally well tolerated, with most adverse effects being minor and self-limiting, there are singular reports on hypersensitivity immune reactions triggered by a PPI or its metabolites. Here we report a case of acute drug-induced fever with leukocytosis and a transient increase in CRP due to pantoprazole. This was apparently an idiosyncratic reaction (inflammatory fever), showing no cross-sensitivity towards esomeprazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Pancreatitis and peripheral edema have also been reported in human patients treated with pantoprazole ( 32 – 34 ). A case of pantoprazole-induced hyperthermia was reported in a human patient, however, none of our study goats had elevated temperatures during the study ( 35 ). While an investigation of adverse effects was beyond the scope of our present study, no gross adverse effects, such as edema or anaphylaxis were observed in this population.…”
Section: Discussionmentioning
confidence: 56%
“…Pancreatitis and peripheral edema have also been reported in human patients treated with pantoprazole ( 32 – 34 ). A case of pantoprazole-induced hyperthermia was reported in a human patient, however, none of our study goats had elevated temperatures during the study ( 35 ). While an investigation of adverse effects was beyond the scope of our present study, no gross adverse effects, such as edema or anaphylaxis were observed in this population.…”
Section: Discussionmentioning
confidence: 56%
“…A wide range of drugs can cause drug fever, but the most commonly associated are antibiotics, anticonvulsants and antiarrhythmic agents [1] . To our knowledge, only one case of drug fever associated with pantoprazole has been reported [3] .…”
Section: Discussionmentioning
confidence: 98%
“…While these drugs have significant benefits to patients suffering from an acute UGIB, significant adverse effects can occur during both short and long-term therapy [6]. The adverse effects of long-term use that have been reported include increased risk of enteric infection, chronic atrophic gastritis, drug-induced lupus, acute interstitial nephritis, thrombocytopenia, and malabsorption of various nutrients like iron, vitamin B12, and magnesium [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%